Modeling the Effects of Land-Cover Change on Rainfall-Runoff Relationships in a Semiarid, Eastern Mediterranean Watershed - Noa Ohana-Levi; Arnon Karnieli; Roey Egozi; Amir Givati; Aviva Peeters (Advances in Meteorology)
Temporal changes and spatial patterns are often studied by analyzing land-cover changes (LCCs) using spaceborne images. LCC is an important factor, affecting runoff within watersheds. The objective was to estimate the effects of 20 years of LCCs on rainfall-runoff relations in an extreme rainfall event. A 1989 Landsat TM-derived classification map was used as input for a Kinematic Runoff and Erosion (KINEROS) hydrological model along with the precipitation data of an extreme rainfall event. Model calibration was performed using measured runoff volume data. Validation of the model performance was conducted by comparing the model results to measured data. A similar procedure was used with a 2009 land-cover classification map as an input to the KINEROS model, along with similar precipitation data and calibration parameters, in order to understand the possible outcomes of a rainfall event of such a magnitude and duration after 20 years of LCCs. The results show an increase in runoff volume and peak discharge between the time periods as a result of LCCs. A strong relationship was detected between vegetation cover and the runoff volume. The LCCs with most pronounced effects on runoff volumes were related to urbanization and vegetation removal.